An Assessment Framework for Benefit Sharing Mechanisms to Reduce Emissions from Deforestation and Forest Degradation within a Forest Policy Mix. (18th October 2017) - Wong, Grace Yee; Loft, Lasse; Brockhaus, Maria; Yang, Anastasia Lucy; Pham, Thu Thuy; Assembe‐Mvondo, Samuel; Luttrell, Cecilia
Abstract: Policy instruments for implementing the Reducing Emissions from Deforestation and Forest Degradation and the enhancement of forest carbon stocks (REDD+) mechanism operate within an orchestra of policy mixes that affect the forest and other land sectors. How will policymakers choose between the myriad of options for distributing REDD+ benefits, and be able to evaluate its potential effectiveness, efficiency and equity (3Es)? This is a pressing issue given the results‐based aspect of REDD+. We present here a three‐element assessment framework for evaluating the outcomes and performance of REDD+ benefit sharing mechanisms, using the criteria of effectiveness, efficiency and equity: (1) the structures (objective and policies) of a REDD+ benefit sharing mechanism; (2) the broader institutional and policy contexts underlying forest governance; (3) outcomes of REDD+ including emission reductions, ecosystem service provision and poverty alleviation. A strength of the assessment framework is its flexible design to incorporate indicators relevant to different contexts; this helps to generate a shared working understanding of what is to be evaluated in the different REDD+ benefit sharing mechanisms (BSMs) across complex socio‐political contexts. In applying the framework to case studies, the assessment highlights trade‐offs among the 3Es, and the need to better manage access to information, monitoring and evaluation, consideration of local perceptions of equity and inclusive decisionmaking processes. The framework does not aim to simplify complexity, but rather serves to identify actionable ways forward towards a more efficient, effective and equitable implementation and re‐evaluation of REDD+ BSMs as part of reflexive policymaking. Copyright © 2017 John Wiley & Sons, Ltd and ERP Environment